Dismantling the dream factory : gender, German cinema, and the postwar quest for a new film language - Baer, Hester (Berghahn Books, 2009)
The history of postwar German cinema has most often been told as a story of failure, a failure paradoxically epitomized by the remarkable popularity of film throughout the late 1940s and 1950s. Through the analysis of 10 representative films, Hester Baer reassesses this period, looking in particular at how the attempt to "dismantle the dream factory" of Nazi entertainment cinema resulted in a new cinematic language which developed as a result of the changing audience demographic. In an era when female viewers comprised 70 percent of cinema audiences a "women's cinema" emerged, which sought to.
Keywords: Motion pictures -- Germany -- History -- 20th century.; Motion pictures -- Social aspects -- Germany -- History -- 20th century.; Motion pictures for women -- Germany -- History -- 20th century.; Motion picture audiences -- Germany -- History -- 20th century.; Women in motion pictures -- History -- 20th century.; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Films de femme -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Publics -- Allemagne -- Histoire -- 20e siècle.; Femmes au cinéma -- Histoire -- 20e siècle.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion picture audiences; Motion pictures; Motion pictures for women; Motion pictures -- Social aspects; Women in motion pictures; Germany; Film history, theory & criticism.; Gender studies, gender groups.; Germany.; Performing Arts.; 1900-1999; History